Exploring adaptive information sharing from the perspective of cognitive switching: The moderating effect of task self-efficacy. Issue 4 (15th July 2019) - Zha, Xianjin; Yang, Haijuan; Yan, Yalan; Yan, Guanxiang; Huang, Chengsong; Liu, Kunfeng
Abstract : Purpose: Microblogging as one kind of social media application provides an important information sharing platform. Adaptive information sharing is the combination of adaptive information technologies (IT) use behavior and information sharing behavior and subsequently refers to adaptive use of IT oriented to information sharing. The purpose of this paper is to understand adaptive information sharing in the context of microblogging from the perspective of cognitive switching. Design/methodology/approach: A research model was developed and survey data were collected. The partial least squares structural equation modeling was employed to verify the research model. Findings: Adaptive information sharing is positively impacted by other people's use, discrepancies and deliberate initiatives among which other people's use is the key determinant. Meanwhile, task self-efficacy positively moderates the effect of other people's use on adaptive information sharing. Practical implications: Developers of microblogging should as far as possible create learning atmosphere and learning culture. With learning atmosphere and culture, more and more users could keep on learning from observing other people. Consequently, more and more users would be willing to try new features of microblogging to share information. Originality/value: This study examines adaptive information sharing by extending adaptive IT use behavior from the levels of technology, system and feature to the information level, presenting a new lens for adaptive IT use and information sharing alike.